2019
DOI: 10.1584/jpestics.d18-048
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation of lysimeter experiments for simulating pesticide dissipation in paddy fields. Part 1: Submerged application of granular pesticides

Abstract: Three-year comprehensive experiments were conducted to compare the dissipation patterns of a total of 16 pesticides, including 3 metabolites, as granular formulations applied in lysimeters and paddy fields with two soil types. Analytical concentrations of the target pesticides in paddy water were analyzed using a granular kinetic model consisting of the following parameters: release rate, decrease rate, and dissolved concentration. Results of parameter grouping analyses of the kinetic models showed that 56% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Finally, the datasets of simetryn and molinate in one of the replicates for the lysimeters (LA‐S1 and LV‐S1 plots in a previous study relabeled as LA and LV plots, respectively) and the paddy fields with alluvial and volcanic ash soils (FA and FV plots) were prepared for the inverse analysis. The detailed experimental design and analytical procedure can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the datasets of simetryn and molinate in one of the replicates for the lysimeters (LA‐S1 and LV‐S1 plots in a previous study relabeled as LA and LV plots, respectively) and the paddy fields with alluvial and volcanic ash soils (FA and FV plots) were prepared for the inverse analysis. The detailed experimental design and analytical procedure can be found elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The applicability of this procedure in the PCPF-1 model is verified by reproducing the dissipation data of granule paddy herbicides obtained from lysimeters and paddy fields under a standard experimental design in Japan. 27,28 Finally, we conduct a case study to improve the current experimental design for a more realistic simulation of the actual condition.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the experiment in 2012 was conducted under a submerged application scenario, and some of the results were reported in the previous report. 1) Table 1 lists the commercial products, their active ingredients, application date, rates, and the theoretical maximum concentration of pesticides (C max ), which was defined as all pesticides were dissolved in paddy water with 5 cm ponding depth. Detailed explanations of the experimental conditions and testplot designs are available in the previous report.…”
Section: Overview Of Experimentsmentioning
confidence: 99%
“…In our previous report, 1) the performance of the flooded lysimeter (hereafter denoted as lysimeter) was compared with that in the actual paddy field involving the submerged application of granular formulations. The results indicated that the current experimental design of the lysimeter could reproduce nearly 50% of the decrease rate of granular pesticides used under actual paddy field conditions, although significant differences in the maximum concentrations were observed owing to variations in hydrological and meteorological factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation